BIOCHEMICAL LIVER TESTS FEATURES IN PATIENTS WITH CHRONIC LYMPHOPROLIFERATIVE DISEASES DEPENDING ON THE PRESENCE OF TUMOR LIVER INFILTRATION - Maslova, G.S.; Skrypnyk, I.M. (World of Medicine and Biology, 2019)
Timely evaluation of liver functional disorders tests and their correct interpretation is of particular importance during specific chemotherapy, as well as during the patients’ recovery after cytostatic treatment. The article presents the results of the authors’ own studies on 16 patients with chronic lymphoproliferative diseases of low-grade malignancy who died in the hematology department of Poltava M.V. Sklyfosovsky Regional Clinical Hospital. A comparative evaluation of hematological and biochemical panel parameters depending on the presence of the liver tumor infiltration according to pathohistological examination. It has been shown that liver tumor infiltration is associated with peripheral blood leukocytosis (p
Keywords: chronic lymphoproliferative diseases; tumor liver infiltration; biochemical liver tests